Comparison of the gut microbiota of obese individuals from different geographic origins. (January 2019) - Angelakis, E.; Bachar, D.; Yasir, M.; Musso, D.; Djossou, F.; Melenotte, C.; Robert, C.; Davoust, B.; Gaborit, B.; Azhar, E.I.; Bibi, F.; Dutour, A.; et al.
Abstract: Few studies have examined the interaction of human geography, microbial community structure and obesity. We tested obese adult volunteers from France, Saudi Arabia, French Polynesia and from a traditional population in the village of Trois-Sauts in French Guiana by sequencing the V3-V4 region. We also sequenced homemade fermented cachiri beers that were obtained from the traditional Amazonian population and are highly consumed by this population. We found that French and Saudis had significantly less richness and biodiversity in their gut microbiota than Amazonians and Polynesians (p <0.05). Principle coordinate analysis of the overall composition of the genera communities revealed that the microbiomes of Amazonians clustered independently from the other obese individuals. Moreover, we found that Amazonians presented significantly stricter anaerobic genera than the Saudis, French and Polynesians (p < 0.001). Polynesians presented significantly lower relative abundance of Lactobacillus sp. than French (p 0.01) and Saudis (p 0.05). Treponema berlinense and Treponema succinifaciens were only present in the gut microbiome of Amazonians. The cachiri beers presented significantly more bacterial species in common with the gut microbiome of Amazonians (p < 0.005). Obese individuals with different origins present modifications in their gut microbiota, and we provide evidence that the cachiri beers influenced the gut microbiome of Amazonians.